2003
DOI: 10.4049/jimmunol.170.9.4638
|View full text |Cite
|
Sign up to set email alerts
|

Naive T Cell Recruitment to Nonlymphoid Tissues: A Role for Endothelium-Expressed CC Chemokine Ligand 21 in Autoimmune Disease and Lymphoid Neogenesis

Abstract: Naive T cells are usually excluded from nonlymphoid tissues. Only when such tertiary tissues are subjected to chronic inflammation, such as in some (but not all) autoimmune diseases, are naive T cells recruited to these sites. We show that the CCR7 ligand CC chemokine ligand (CCL)21 is sufficient for attracting naive T cells into tertiary organs. We performed intravital microscopy of cremaster muscle venules in T-GFP mice, in which naive T cells express green fluorescent protein (GFP). GFP+ cells underwent sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 60 publications
10
148
1
Order By: Relevance
“…We observed, in keeping with previous reports [20,21], that CCL21 expression was associated with scattered or clustered cells (Fig. 6A, B) as well as with vascular structures (Fig.…”
Section: Ccl21 In Situ Production and Microstructural Lymphoid Organisupporting
confidence: 93%
See 2 more Smart Citations
“…We observed, in keeping with previous reports [20,21], that CCL21 expression was associated with scattered or clustered cells (Fig. 6A, B) as well as with vascular structures (Fig.…”
Section: Ccl21 In Situ Production and Microstructural Lymphoid Organisupporting
confidence: 93%
“…Some of these scattered nonvascular CCL21 + cells, whose phenotype is currently under investigation, appeared irregular in shape, with prolonged cytoplasmic processes (not shown). Although it has been suggested that CCL21 may play a role in ectopic lymphoid neogenesis in RA synovium [20,21], no comparative analysis between the vascular and nonvascular pattern was carried out in those studies. Our systematic in situ analysis demonstrated that nonvascular CCL21-producing cells were specifically associated with lymphoid aggregates; they were only rarely or were not detected in the sublining stroma devoid of a consistent mononuclear infiltrate.…”
Section: Ccl21 In Situ Production and Microstructural Lymphoid Organimentioning
confidence: 99%
See 1 more Smart Citation
“…). Structurally mature ELFs are not, however, seen in skin conditions despite local expression of Ccl21 , which suggests that the immune setting and the interaction of the stromal compartment with resident and infiltrating cells has to be conducive for ELF development to occur 56, 57. This may reflect differences in innate sensing responses or a differential stromal response to chemokines and cytokines necessary for the initiation, expansion and maintenance of tissue ELFs.…”
Section: Homeostatic Chemokines In Elf Developmentmentioning
confidence: 99%
“…As a control, mice were injected in the contralateral inguinal mammary fat pad with vehicle alone as previously reported (38,39).…”
Section: In Vivo Treatment With Ccr7 Antagonistmentioning
confidence: 99%